Isolation and Study of the Phenotypic Characteristics of Some Soil-borne Fungi in two Different Locations in Omar AL-Mukhtar University, Albyda, Libya - Hasan, Zainap Ab. Eesa (Scientific Journal for Faculty of Science-Sirte University, 2024)
Fungi play a crucial role in the terrestrial ecosystem, and they are responsible for many key steps in the maintenance of ecosystem stability, particularly by recycling the soil organic matter and mineral elements. Omar AL-Mukhtar University is located at Albayda city, eastern Libya. Where the diversity of soil fungal in this region has not yet been investigated. In this study, soil samples were collected from two different locations of university. Soil fungi were isolated using the soil dilution soil technique and PDA agar medium. As light difference in diversity of fungal was observed between both sites, where outcomes showed that the dominant genera detected belonged to the Ascomycota with fewer proportions belonging to Zygomycota. The frequent species were in decreasing order; Aspergillus, Penicillium spp, and Trichoderma spp.